A Case of Chronic Incomplete Vogt-Koyanagi-Harada (VKH) Disease with Systemic Involvement in a 57-Year-Old Woman - Prakoeswa, Camilla A.; Zuhria, Ismi (Vision Science and Eye Health Journal, 2025)
Introduction: Vogt–Koyanagi–Harada (VKH) disease is a systemic disorder that involves tissues containing pigmented cells. It is thought to be caused by an autoimmune T-cell-mediated process against melanocytes in systemic organs, particularly the eyes. VKH disease is a chronic, bilateral, diffuse, granulomatous panuveitis that involves integumentary, neurologic, and auditory aspects, which affects females and darkly pigmented ethnic groups. Here, we presented a rare case of VKH disease in a seronegative spondyloarthropathy patient. Case Presentation: A 57-year-old woman complaining of blurry vision in both eyes for three years. She was previously diagnosed with spondyloarthropathy, osteoarthritis, type 2 diabetes, hypertension, and dyslipidemia. Both eyelids exhibited periocular vitiligo and poliosis and were slightly hyperemic. Both eyes had perilimbal vitiligo and fine brown keratic precipitates. The anterior chambers were deep and quiet; however, the patient had posterior synechiae in both eyes. The fundus examination showed a sunset glow fundus appearance. Conclusions: VKH is a chronic disease that can relapse and recur. While the disease's prognosis is overall favorable, it is determined by the duration and frequency of recurrent inflammation episodes; thus, early detection and prompt treatment are essential for success. Poor visual prognosis is predicted by a larger number of complications, an older age at disease onset, a longer median duration of the disease, delayed treatment initiation, and a higher number of recurrent episodes of inflammation. To preserve vision, patients often require lifelong immunosuppressive therapy and need to be educated about the signs and symptoms to watch for when their condition relapses.